Weak local Nash equilibrium - Biasi, Carlos; Monis, Thaís Fernanda Mendes [UNESP] (My University, 2013)
In this paper, we consider a concept of local Nash equilibrium for non-cooperative games - the so-called weak local Nash equilibrium. We prove its existence for a significantly more general class of sets of strategies than compact convex sets. The theorems on existence of the weak local equilibrium presented here are applications of Brouwer and Lefschetz fixed point theorems. © 2013 Juliusz Schauder Centre for Nonlinear Studies Nicolaus Copernicus University.
Keywords: Fixed point; Nash equilibrium; Proximative retract